Hubungan Sumber Informasi Pasangan Usia Subur Dengan Pemilihan Kontrasepsi Jangka Panjang di Puskesmas Baamang 2 Sampit Tahun 2024 - Puspita Sari Pribadi; Tri Agustin (Pusat riset dan Inovasi Nasional, 2025)
The high birth rate is one of the big challenges for the State of Indonesia in the family planning program that is recommended to control population growth, including the application of the Long-Term Contraceptive Method (MKJP) (BKKBN, 2016). In 2023, the total population of Indonesia is 278.8 million people. This number increased by 1.1% compared to 2022 which was 275.5 million people. In Central Kalimantan, in 2023, there will be 327,182 couples of childbearing age (PUS), then 244,374 active family planning (PA) users and 902 new contraceptive devices (PB).. East Kotawaringin Regency itself recorded the most active family planning participants in injectable birth control (82.0%), pills (13.7%), implants (2.9%), condoms (0.3%), AKDR (0.6%), MOP contraception (0.2%), and MOW (0.3%), recorded participants who use MKJP in Kotim only (4%) of the total number of family planning participants (Kotim Health Profile, 2022). Some of the factors that cause the low selection of MKJP include individual perception, husband support, knowledge, education, work and attitude. The purpose of this study is to determine the relationship between the source of information on couples of childbearing age and the selection of long-term contraception at the Baamang 2 Sampit Health Center in 2024. A type of quantitative analytical research with a cross-sectional research design.The population in the study was all family planning acceptors at the Baamang 2 Sampit Health Center. The sample in this study was by accidental sampling technique and a sample of 37 people was obtained. The statistical test of this study is the chi-square test. The results of univariate analysis from 37 people mostly obtained direct sources of information as many as 23 people (62.2%), the majority of those who used Non-MKJP family planning as many as 24 people (64.9%) and the results of bivariate analysis obtained a ρ value of 0.74. There is no relationship between the source of information on couples of childbearing age and the selection of long-term contraception at the Baamang 2 Sampit Health Center in 2024.